Analisa Penggunaan Daya Listrik pada KM. Jaya Utama 66 Berdasarkan Electric Balance BKI - Mohamad Haris; Jozua Ch Huwae; Fahriadi Pakaya; Yurika Nantan (Zona Laut : Jurnal Inovasi Sains Dan Teknologi Kelautan, 2023)
Jaya Utama 66 is a fishing vessel that operates in the sea waters of Maluku to Merauke. Analysis of the demand for electric power in KM. Jaya Utama 66 to prevent blackout conditions when the ship is operating and in selecting a generator as a source of ship power generation is very necessary. The purpose of this practical work is to know the working principle of the generator, to know the electricity distribution system and to be able to analyze the use of electric power in KM. Jaya Utama 66. Based on data obtained from observations and collection of equipment power loads on KM. Jaya Utama 66, the generator set has the principle of a rotor that rotates in a magnetic field and creates an electric force (EMF). Electromotive force is an electric action produced by a non-electric source. Electrical distribution system in KM. Jaya Utama 66 is sourced from the generator and then flowed to the main switch board and distributed to the connecting panel, then the electric power is divided between the loads of electrical equipment. The calculation results show that the ratio of Power consumption equipment is 80% with the Divercity Factor value according to the conditions of in&out ports, sailing, loading and unloading, and berthing above 0.50 and the Generator Load factor in ship operations is still feasible and according to the standards set by BKI which cannot be more of 80%.